Develop Algorithm RSA to Ensure Authentication and Smooth Flow Data (Journal of Hama University, 2019)
The RSA algorithm relies on key generation then process of encryption by fragmenting message and applying cryptographic equation on each part of the message.but this operation negatively effects on speed of the encryption process, thus reducing the flow of the data level that require to be protected and transmit over the network. When conducting a verification of the sender and receiver of blocks of data, this research provides a proposed mechanism for the development of the RSA algorithm to ensure that the sender and the receiver of the data is verified with a high level of flow, the developed mechanism has proved superior to the RSA algorithm For protection of data by 0.56 seconds for the encryption process and 0.48 seconds for the decryption process, and for protection and verification, 1.202 seconds for encryption time and 0.936 seconds for decoding time for five different text documents In size